Pola dan Sistem Pemeliharaan Ternak Sapi Bali di Kabupaten Muna - La Ode Muhammad Munadi; Hidayat Hidayat; La Ode Sahaba; Inal Inal (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2021)
The livestock sector is a potential in the provision of animal origin food and is a source of income for farmers. The research was conducted in Muna Regency from October to December 2020 aimed to see the pattern and system of livestock maintenance using survey methods by determining samples using purposive sampling as many as 150 respondents spread in Muna Regency. The type of data used in the form of primary data and secondary data is obtained from the results of research and literature studies through the help of quisioners. The data obtained is then analyzed descriptively. The results showed that livestock maintenance system is divided into 3 intensive parts as much as 4%, semi-intensive 49,9% and extensive 46,1% with a maintenance pattern of 96,009% nurseries, and 3,991% fattening.